Edukasi Penegakan Hukum Yang Berkeadilan Sebagai Upaya Meningkatkan Kesadaran Hukum Siswa Kelas VI SDN Rawamangun 12 Pagi - Firly Aurellia Rahma; Muhammad Ridwan Sarkhozi; Naura Zalfa Alamunda; Rizky Yasyakiib Yusuf; Verlyta Salsabila; M. Fikri Akbar (JURNAL ABDIMAS DOSMA (JAD), 2026)
Legal awareness is an essential aspect of character development among students from an early age. However, some elementary school students still have a limited understanding of the importance of law, justice, and compliance with rules in their daily lives. This observational activity aimed to enhance students’ understanding of legal concepts and increase their legal awareness through a socialization program on fair law enforcement. The observation was done towards sixth-grade students at SDN Rawamangun 12 Pagi using an educational and participatory approach. The methods employed included material presentation and interactive discussions through question-and-answer sessions. The results indicated an improvement in students’ understanding of the concepts of law and justice, increased student participation throughout the activity, and greater awareness of the importance of obeying rules and applying the values of justice in both school and community settings. This activity contributed positively to strengthening character education and fostering a culture of legal awareness among elementary school students.